Towards a Robust Computer Security Layer for the Lin Bus - Paez-Mejias, F; Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2021)
The increasing local and remote wireless connection possibilities available to common vehicles (such as cellular, Bluetooth, V2X communication) have raised significant cybersecurity concerns. This paper presents an up-to-date compilation about security vulnerabilities present in the most relevant in-vehicle communication buses (CAN, LIN, FlexRay), and a summary of various cybersecurity proposals for CAN and FlexRay, from various authors. Possible cyberattacks on the LIN bus are presented in detail, in order to outline the design of a robust IT security layer for this bus, thereby significantly contributing to the safety of vehicle occupants. © 2021 IEEE.
Keywords: Computer security; CAN; FlexRay; in-vehicle networking; LIN